2013
DOI: 10.1007/s10753-013-9766-0
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Toll-Like Receptors: Porphyromonas gingivalis Induces IL-6, IL-8, and VCAM-1 Expression Through NOD-Mediated NF-κB and ERK Signaling Pathways in Periodontal Fibroblasts

Abstract: To investigate whether oligomerization domains (NODs) are involved in Porphyromonas gingivalis-induced interleukin (IL)-6, IL-8, and vascular cell adhesion molecule (VCAM)-1 expression beyond Toll-like receptors (TLRs), we investigated the role of NOD1/2 in P. gingivalis-induced IL-6, IL-8, and VCAM-1 expression in human gingival fibroblasts (hGFs) and periodontal ligament cells (hPDLCs). The mechanism was explored by activation and silence of NODs, electrophoretic mobility shift assay (EMSA), and pathway bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 43 publications
4
44
0
1
Order By: Relevance
“…The virulence factors and intact cells of P. gingivalis could stimulate PDLFs to produce inflammatory cytokines. 31,39 The live P. gingivalis would digest the cytokines in the cell suppuration. Yee et al found that the secretion of IL-6 and IL-8 by P. gingivalis challenged oral epithelial cells was higher in 6 h and 24 h than that in control cells, and heat-inactivated P. gingivalis upregulated more IL-6 and IL-8 secretion in the cells than the live P. gingivalis challenged groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The virulence factors and intact cells of P. gingivalis could stimulate PDLFs to produce inflammatory cytokines. 31,39 The live P. gingivalis would digest the cytokines in the cell suppuration. Yee et al found that the secretion of IL-6 and IL-8 by P. gingivalis challenged oral epithelial cells was higher in 6 h and 24 h than that in control cells, and heat-inactivated P. gingivalis upregulated more IL-6 and IL-8 secretion in the cells than the live P. gingivalis challenged groups.…”
Section: Discussionmentioning
confidence: 99%
“…Yee et al found that the secretion of IL-6 and IL-8 by P. gingivalis challenged oral epithelial cells was higher in 6 h and 24 h than that in control cells, and heat-inactivated P. gingivalis upregulated more IL-6 and IL-8 secretion in the cells than the live P. gingivalis challenged groups. 19 Scheres et al 25 and Liu et al 39 found that mRNA expression of IL-6 and IL-8 in PDLFs was up-regulated after live P. gingivalis stimulation. Our results showed that IL-6 and IL-8 protein expression simulated by live P. gingivalis was significantly higher than controls from 6 to 12 h. Therefore, we speculate that P. gingivalis could initiate the .…”
Section: Discussionmentioning
confidence: 99%
“…and its essential component lipopolysaccharide (LPS) have been identified as the major periodontal pathogenic factors that aggravate periodontitis . LPS induces PDLCs to activate the NF‐κB signaling pathway and its downstream target genes, such as interleukin (IL)‐6 and IL‐8 . IL‐6 is capable of inducing osteoclastogenesis, and IL‐8 is a major chemoattractant of neutrophils .…”
Section: Introductionmentioning
confidence: 99%
“…Palmitic acid could induce human HaCaT keratinocytes to produce proinflammatory cytokines IL-6, IL-1β, and TNF-α in a dose-dependent manner via activation of NF-κB [15]. P. gingivalis induced IL-6, IL-8, and VCAM-1 expression in human gingival fibroblasts and human PDL cells through the NOD1/2-mediated NF-κB and ERK1/2 signaling pathways [16]. These data suggest that IL-1β and IL-8 play critical roles in the pathological changes in periodontitis and α7 nAChR/NF-κB pathway might regulate these cytokines.…”
Section: Introductionmentioning
confidence: 99%